Пчела и мёд в народной культуре: коллективная монография / авторский коллектив: Абсалямова Ю. А., Анисимов Н. В., Анфиногенов Б. В. [и др.] - Абсалямова Юлия Аликовна (УдмФИЦ УрО РАН, 2023)
Экземпляры: КР (20240115) / Инвентарный номер: 1127987 / Цена: / Сис.шифр: 63.5 / Авт.знак: П 92 / ГРНТИ: 03 / ББК: 63.529(235.5)